(untitled) (Global Journal of Human-Social Science, 2021)
The present study aims to evaluate the position of Algeria in the knowledge economy, which is seen as an inevitability to strengthen competitiveness and achieve economic development. In this context, we try through this study firstly to know the impact of the knowledge economy on competitiveness, applying the Knowledge-Based Economy Indicator (KEI index) according to the World Bank methodology, and the competitiveness indicator according to the World Economic Forum report (GCI index), which will allow us to compare Algeria with indicator countries. The study is realized by using descriptive statistics, correlation, regression and comparative analysis. The study is composed of the following parts: analysis of the competitiveness of Algeria and comparative countries according to the GCI and the KEI, as well as according to the pillars within the KEI, examination of interdependence GCI and KEI and an examination of the impact of the pillar within the KEI on GCI in Algeria and comparative countries. Research results indicate that there is a medium positive correlation between the GCI and KEI. The results of this study provide recommendations to the policy makers in Algeria and comparative countries.